Quantitative reflections on recent Guatemalan political history : A CIIDH/AAS Report - Ball, Patrick (1998)
Guatemala is a country of massive labor migration. Workers frequently travel many hours by foot and bus to spend weeks working in areas far from their homes in agricultural wage labor.In places where such labor is common, it might be true that political violence could target the migrant workers in order to maintain control of the work force. In counties (municipios) with high rates of wage labor ,this theory would predict that among victims of political violence, there should be a higher rate of migrants.